2019
DOI: 10.3168/jds.2019-16866
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recycled manure solids bedding on the spread of gastrointestinal parasites in the environment of dairies and milk

Abstract: The primary aim of this work was to isolate common bovine digestive tract parasites in recycled manure bedding (RMS), as well as to determine the ability of current RMS preparation procedures to eliminate these pathogens. Other objectives were to assess whether any of the aforementioned parasites could be retrieved in bulk milk from dairies using RMS and to study whether the prevalence of these parasites differed among manure of cows housed on RMS versus on straw bedding. For the study, 27 RMS farms and 61 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
1
18
1
Order By: Relevance
“…Infection of calves with a large number of oocysts of E. zuernii or E. bovis may lead to severe diarrhea including blood, intestinal tissue, and fibrin [ 16 ]. Lasprilla-Mantilla et al have also proven this conclusion [ 40 ], which is consistent with our research results; however, the difference in our own analysis was not statistically significant. In our study, E. bareillyi had the highest prevalence, which may be due to the fact that the total number of samples taken in the study of E. bareillyi is only 50 cattle, and the total number of samples is too small, which leads to biased research results.…”
Section: Discussionsupporting
confidence: 93%
“…Infection of calves with a large number of oocysts of E. zuernii or E. bovis may lead to severe diarrhea including blood, intestinal tissue, and fibrin [ 16 ]. Lasprilla-Mantilla et al have also proven this conclusion [ 40 ], which is consistent with our research results; however, the difference in our own analysis was not statistically significant. In our study, E. bareillyi had the highest prevalence, which may be due to the fact that the total number of samples taken in the study of E. bareillyi is only 50 cattle, and the total number of samples is too small, which leads to biased research results.…”
Section: Discussionsupporting
confidence: 93%
“…The maintenance system was litter-free boxing with the possibility of mulching a bed of approximately 0.5 kg of separator per cow per day. The recycled manure bedding (RMS) was safe in bacteriological terms and free of parasites and did not cause any deterioration in milk quality [18][19][20][21]. It combined two advantages: it improved the comfort of cows' rest with litter material savings.…”
Section: Description Of the Milk Cow Farming Systemmentioning
confidence: 99%
“…There are few studies on the association between RMS usage and animal health. It was demonstrated that Cryptosporidium parasites were found more frequently from the feces of cows in RMS farms compared with cows housed on straw bedding ( 6 ). In the same project, the presence of Listeria monocytogenes and Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…The objectives of this study were, therefore, to describe the total incidence of CM in dairy cows housed on recycled manure solids bedding and CM incidence by the main bacterial species and to compare these to herds using a more conventional type of bedding, straw. The results presented in this paper are part of a larger study on RMS farms, and results about milk quality, parasite survival, and bedding bacteriological analyses can be found elsewhere ( 6 , 11 ).…”
Section: Introductionmentioning
confidence: 99%